A Theoretical examination of police entry-level uncorrected visual acuity standards - Cox, Terry C. (American journal of criminal justice, 1987)
Police organizations function in a dynamic environment that requires management to make adjustments to constant changes. The focus of this paper is on entry-level uncorrected vision entry standards that are being affected by recent technological advancements in the optical field. Extreme policy variances exist relative to - these requirements and many of the more rigid policies are grounded in unrealistic foundations. Many of these foundations relate to problems relevant to spectacles. Additionally, these standards are based on very remote events. An analysis of these policies and policy recommendations are presented in this paper.